Sadet phrarātchadamn̄œn Pākīsathān, Sahaphantharat Malāyā Ph̨ō. S̨ō. 2505 - Prak̨̄op Hutasing, 1911-1994 (Samnak Phrarātchawang], 1996)
On the state visits to Pakistan and The Federation of Malaya in 1962 of Bhumibol Adulyadej, King of Thailand, b. 1927; cremation volume for Prak̨ōp Hutasing, 1911-1994, former Deputy Prime Minister of Thailand.